Correction to: Assessment of HIF-1α expression and release following endothelial injury in-vitro and in-vivo - Lamia Heikal; Pietro Ghezzi; Manuela Mengozzi; Gordon Ferns (Molecular Medicine, 2020)
An amendment to this paper has been published and can be accessed via the original article.